Case Study: Evidence-Based Interventions Enhancing Diabetic Foot Care Behaviors among Hospitalized DM Patients - Kurniawan, Titis; Petpichetchian, Wongchan (Nurse Media Journal of Nursing, 2011)
Background: Improving diabetic patients’ foot care behaviors is one of the most effective strategies in minimizing diabetic foot ulceration and its further negative impacts, either in diabetic hospitalized patients or outpatients.Purpose: To describe foot care knowledge and behaviors among hospitalized diabetic patients, to apply selected foot care knowledge and behaviors improvement evidence, and to evaluate its effectiveness.Method: Four diabetic patients who were under our care for at least three days and could communicate in Thai language were selected from a surgical ward in a university hospital. The authors applied educational program based on patients’ learning needs, provided diabetic foot care leaflet, and assisted patients to set their goal and action plans. In the third day of treatment, we evaluated patients’ foot care knowledge and their goal and action plan statements in improving foot care behaviors.Result: Based on the data collected among four hospitalized diabetic patients, it was shown that all patients needed foot care behaviors improvement and the educational program improved hospitalized patients’ foot care knowledge and their perceived foot care behaviors. The educational program that combined with goal setting and action plans method was easy, safe, and seemed feasibly applicable for diabetic hospitalized patients.Conclusion: The results of this study provide valuable information for improvement of hospitalized diabetic patients’ foot care knowledge and behaviors. The authors recommend nurses to use this evidence-based practice to contribute in improving the quality of diabetic care.Keywords: Intervention, diabetic foot care, hospitalized diabetic patients